Encyclopedia of nature (DK Multimedia, 1997)
Provides interactive exploration of the fascinating lives of hundreds of species of animals and plants and the habitats in which they live. Includes video sequences, animation, photographs, bird calls, a 3D interface and over 1800 articles.